Comparing Nucleophilicity of Heavier Heteroleptic Amidinato‐Amido Tetrelylenes: An Experimental and Theoretical Study. Issue 9 (27th June 2016) - Parvin, Nasrina; Pal, Shiv; Rojisha, Vallyanga Chalil; De, Susmita; Parameswaran, Pattiyil; Khan, Shabana
Abstract: In our previous communication we have reported the isolation and reactivity of heteroleptic three coordinated silylene, LSi(2, 6‐ i Pr2 C6 H3 NPPh2 ) [L= PhC(N t Bu)2 ] (2 ). Here we report the isolation of analogous germylene and stannylene, LGe(2, 6‐ i Pr2 C6 H3 NPPh2 ) (6 ) and LSn(2, 6‐ i Pr2 C6 H3 NPPh2 ) (7 ) from the reaction of 2, 6‐ i Pr2 C6 H3 N(Li)PPh2 (1 ) with LGeCl (4 ) and LSnCl (5 ), respectively. Both compounds are characterized by multinuclear NMR spectroscopy, EI‐mass spectrometry, and single crystal X‐ray diffraction studies. The comparison of the molecular orbitals and the molecular electrostatic potential (ESP) maps on the van der Waal's surface of the atoms in silylene (2 ), germylene (6 ), and stannylene (7 ) indicate that nucleophilicity of the group‐14 atom reduces from silylene to stannylene. The Si‐center is more nucleophilic than P‐center in2, whereas Ge and P‐ centers have similar nucleophilicity in6 and Sn‐center is much less nucleophilic than P‐center in7 . The global minimum of the ESP of2 is in the direction of the lone pair on Si, whereas the global minimum of the ESP of6 and7 is located above 2, 6‐ i Pr2 ‐C6 H3 ring on the N‐atom and in the opposite direction of the P‐center. This is supported by the observation that silylene2 forms complex with AuCl by coordinating with Si‐center, whereas germylene6 and stannylene7 do not form the analogous adducts. Abstract : Amidinato‐amido supported germylene and stannylene derivatives have been prepared and compared for their nucleophilicity.